2000
DOI: 10.1021/cc000012g
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Addressed Synthesis of Amino- and Amino-Oxy-Substituted 1,3,5-Triazine Arrays on Polymeric Membranes

Abstract: Effective spatially addressed parallel assembly of trisamino- and amino-oxy-1,3,5-triazines was achieved by applying the SPOT-synthesis technique on cellulose and polypropylene membranes. In addition to developing a suitable linker strategy and employing amines and phenolate ions as building blocks, a highly effective microwave-assisted nucleophilic substitution procedure at membrane-bound monochlorotriazines was developed. The 1,3, 5-triazines obtained could be cleaved in parallel from the solid support by TF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(71 citation statements)
references
References 16 publications
1
69
0
1
Order By: Relevance
“…[223,224] Apart from traditional cross-linked polystyrene resins a number of different supports and formats have been used in microwave-assisted SPOS. These include tentagel resins, [117,213,214,225] cellulose membranes (SPOT synthesis), [226,227] cellulose beads, [228] and glass surfaces. [229] Janda and co-workers have described the use of JandaJel as the support in the solid-phase synthesis of oxazoles (Scheme 48).…”
Section: Methodsmentioning
confidence: 99%
“…[223,224] Apart from traditional cross-linked polystyrene resins a number of different supports and formats have been used in microwave-assisted SPOS. These include tentagel resins, [117,213,214,225] cellulose membranes (SPOT synthesis), [226,227] cellulose beads, [228] and glass surfaces. [229] Janda and co-workers have described the use of JandaJel as the support in the solid-phase synthesis of oxazoles (Scheme 48).…”
Section: Methodsmentioning
confidence: 99%
“…But, it was observed that this gradient did not affect the particular chemistry (Glass & Combs, 2001). Wenschuh et al (2000) have synthesised a library of trisamino-and amino-oxy-1,3,5-triazines with 8000-members in their study, by carrying out microwave-assisted nucleophilic substitution at cellulose-membrane-bound monochlorotriazines. Microwave assisted substitution of the chlorine atom in monochlorotriazines is the major step in this reaction.…”
Section: Parallel Processing In Microwave Reactorsmentioning
confidence: 99%
“…This technique features chemical synthesis at defined "spots" on a solid support, such as cellulose (e.g., filter paper). Polypropylene membranes have also been used to increase the chemical and mechanical stability between the attached molecule and the membrane (Scharn et al, 2000). For example, for SPOT synthesis of peptide libraries, the activated amino acids are dotted at specific positions onto a functionalized membrane forming a "spot" within which miniscale coupling reactions can proceed.…”
Section: Spot-synthesismentioning
confidence: 99%
“…Conventional solid phase peptide synthesis proceeds with each additional amino acids added directly to the defined spots. Linkers can also be included on the functionalized membrane to allow cleavage and recovery of the synthesized product Scharn et al, 2000). This method has been employed for a number of applications ranging from the identification of proteinprotein interactions, development of protein mimics (Bracci et al, 2001), optimization of peptide spotting densities, improved reproducibility, increased signal intensities (Kramer et al, 1999) and enzyme-substrate recognition (Reineke et al, 2001).…”
Section: Spot-synthesismentioning
confidence: 99%